Harmful signaling in matching markets - Alexey Kushnir (Fondazione Eni Enrico Mattei (FEEM), 2010)
Some labor markets have recently developed formal signalling mechanisms, e.g. the signalling for interviews in the job market for new Ph.D. economists. We evaluate the effect of such mechanisms on two-sided matching markets by considering a game of incomplete information between firms and workers. Workers have almost aligned preferences over firms: each worker has 'typical' commonly known preferences with probability close to one and 'atypical' idiosyncratic preferences with the complementary probability close to zero. Firms have some commonly known preferences over workers. We show that the introduction of a signalling mechanism is harmful for this environment. Though signals transmit previously unavailable information, they also facilitate information asymmetry that leads to coordination failures. As a result, the introduction of a signalling mechanism lessens the expected number of matches when signals are informative.
Keywords: C72; C78; D80; J44; 330; Signaling; Cheaptalk; Matching